Lymphovenous Anastomosis Bypass Surgery - Chang, Edward I.; Skoracki, Roman J.; Chang, David W. (Seminars in Plastic Surgery, 2018)
The field of lymphedema surgery has witnessed tremendous advancements over the years and has been coupled to the rapid growth of supermicrosurgical techniques. A lymphovenous bypass or lymphaticovenular anastomosis is a new technique that requires identification of patent, residual lymphatic channels and performing an anastomosis to a recipient venule, thereby allowing outflow of lymphatic fluid and improvement in a patient's lymphedema. This article provides a summary of the maturation of the technique, as well as the technical aspects of the approach and the current outcomes in the treatment of postmastectomy lymphedema.
Keywords: lymphedema surgery; lymphovenous bypass; lymphaticovenular anastomosis